The Influence of Islamic Education on the Formation of Adolescent Character Amid Globalization Challenges - Lukman Nol Hakim; Endin Mujahidin; Budi Handrianto (Lafadz Jaya Publisher, 2024)
This study explores the influence of Islamic education on the character formation of adolescents in the context of the challenges posed by globalization. The rapid advancement of technology and the increasing exposure to global values have raised concerns about the erosion of traditional values, particularly in the younger generation. This research aims to investigate how Islamic educational institutions contribute to strengthening the moral and ethical values of adolescents in the face of these challenges. Using a mixed-methods approach, data were collected through surveys and interviews with adolescent students in Islamic schools, focusing on their perceptions of character development, the role of religious teachings, and their ability to navigate modern societal influences. The findings suggest that Islamic education plays a crucial role in shaping the character of adolescents, especially in fostering a strong sense of responsibility, respect for others, and resilience against negative external influences. The study highlights the importance of integrating Islamic values into education as a countermeasure to the negative effects of globalization. This research contributes to the understanding of how religious education can serve as a foundation for developing moral character, offering practical insights for educators, policymakers, and parents aiming to guide adolescents through the complexities of contemporary society.